Exploration of Potential Fishing Grounds of Yellowfin Tuna (Thunnus Albacares) Using Satellite Data to Enable Diversification of Fishing Efforts Towards Deep Sea in the Bay of Bengal - Farejiya M.K; Vinod Kumar Mudumala; R. M. Dwivedi; Kiran S. Mali (Journal of Indian Fisheries Association, 2023)
Long line fishing operations for Yellowfin tuna were carried out by the Fishery Survey of India in oﬀ shore waters of the Bay of Bengal (5°-20°N, 80°-90°E.) as a part of exploratory fishery resources surveys during the period from February 2016 to January 2017, the hooking rates were in the range 0-9.5 %. Catches greater than a sum of mean and standard deviation (1.6%) in the sample were considered high. In order to understand the basis for intense accumulation of tuna in the deep waters; the geo referenced catch data were located on chlorophyll and SST (sea surface temperature) images of the respective dates generated from MODIS Aqua data. Unusually high hooking rates of Yellowfin tuna were attributed to the areas under cyclonic rotation of water mass and warmer side of the meandering front. Moreover, hooking rates were at the peak (9.5 %) when fishing was performed in the waters under influence of diatom bloom during December 2016. The other highlight of this paper is application of the concept developed for exploration of deep sea tunas using satellite colour/thermal gradients associated with the prevailing physical process. This paper provides information on the relationship between SST, chlorophyll, diatoms and YFT catch. This can be used to identify potential oceanic fishing grounds for YFT in the Bay of Bengal.